Strategi Pemerintah Daerah Kabupaten Bintan dalam Mengurangi Angka Pengangguran di Kabupaten Bintan - Aslinda Aslinda; Afrizal Afrizal; Eki Darmawan (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2024)
Bintan Regency is a Regency with the largest decrease in the open unemployment rate for the 2022-2023 period in the Riau Islands. This study aims to determine the strategy of the Bintan Regency Regional Government in reducing unemployment in Bintan Regency. The research method used is qualitative descriptive research with interview and documentation data collection techniques. The results of this study indicate that the Bintan Regency Manpower Office has mostly implemented its strategy well from the organizational strategy already having good strategies and policies. The program strategy has a positive impact on the workforce in improving skills and prioritizing the placement of local workers. The resource support strategy is adequate both in terms of human resources, finance, technology and infrastructure. Institutional strategy, responsible for performance targets and exercising its authority in reducing unemployment.